Phylogenetic and phenotypic characterization of Burkholderia pseudomallei isolates from Ghana reveals a novel sequence type and common phenotypes - Schully, Kevin L.; Voegtly, Logan J.; Rice, Gregory K.; Drumm, Hannah; Fitzpatrick, Maren C.; Malagon, Francisco; Shea, April; Dong, Ming; Oduro, George; Robberts, F. J. Lourens; Dartey, Paul K. A.; Owusu-Ofori, Alex; et al. (Frontiers in Microbiology, 2024)
Melioidosis is a potentially severe disease caused by the gram-negative soil-dwelling bacterium called Burkholderia pseudomallei. The true breadth of the distribution of this tropical pathogen is starting to emerge with environmental and clinical isolates frequently characterized in new countries and regions. Even so, isolates, clinical cases, and genetic data from the continent of Africa remain scant. We previously confirmed the presence of B. pseudomallei in the environment of Ghana, unmasking a new area of endemicity for this pathogen. Here, we describe the genetic characteristics of isolates obtained from that environmental survey.Twenty-one isolates were subjected to whole genome sequencing and found to represent three discrete sequence types (ST), one of which was novel, and designated ST2058. Phylogenetic analysis places this novel isolate within a B. pseudomallei clade that includes genomes derived from the Americas, although it is closely related to a sub-clade that includes isolates from Africa. Importantly, phenotypic characterization demonstrates common features including API 20NE profiles and B. pseudomallei CPS to support existing diagnostics, and susceptibility to standard of care antibiotics often used in the clinical management of melioidosis. These findings add to our knowledge about the presence and distribution of B. pseudomallei in Africa and represent the first published genomes out of Ghana.